Development of depot PLGA-based in-situ implant of Linagliptin: Sustained release and glycemic control - Eman Gomaa; Noura G. Eissa; Tarek M. Ibrahim; Hany M. El-Bassossy; Hanan M. El-Nahas; Margrit M. Ayoub (Elsevier, 2023)
High percentage of diabetic people are diagnosed as type 2 who require daily dosing of an antidiabetic drug such as Linagliptin (Lina) to manage their blood glucose levels. This study aimed to develop injectable Lina-loaded biodegradable poly (lactic-co-glycolic acid) (PLGA) in-situ implants (ISIs) to deliver a desired burst effect of Lina followed by a sustained release over several days for controlling the blood glucose levels over prolonged time periods. The morphological, pharmacokinetic, and pharmacodynamic assessments of the Lina-loaded ISIs were performed. Scanning electron microscopy (SEM) study revealed the rapid exchange between the water miscible solvent (N-methyl-2-pyrrolidone; NMP) and water during the ISI preparation, hence enhancing the initial burst Lina release. While, triacetin of lower water affinity could lead to formation of more compact and dense ISI structure with slower drug release. By comparing various ISI formulations containing different solvents and different PLGA concentrations, the ISI containing 40 % PLGA and triacetin was selected for its sustained release of Lina (93.06 ± 1.50 %) after 21 days. The pharmacokinetic results showed prolonged half life (t1/2) and higher area under the curve (AUC) values of the selected Lina-loaded ISI when compared to those of oral Lina preparation. The single Lina-ISI injection produced a hypoglycemic control in the diabetic rats very similar to the daily oral administration of Lina after 7 and 14 days. In conclusion, PLGA-based ISIs confirmed their suitability for prolonging Lina release in patients receiving long-term antidiabetic therapy, thereby achieving more enhanced patient compliance and reduced dosing frequency.